An Unusual Cause of Acute Unilateral Limb Weakness with Altered Sensation in a Young Lady - Zarkasi, Zaiem Akmal (International Journal of Human and Health Sciences (IJHHS), 2021)
This case reports an acute onset of unilateral weakness in a 28-year-old lady who was found collapsed on the floor, unconscious. Initial examination revealed a right-sided facial droop, arm and leg weakness and right leg drift. There was also a decreased sensation in her right forearm. She has no significant past medical history and is not on any regular medications. She was transferred to the nearest emergency department for an urgent stroke assessment. The first CT brain did not show any acute ischaemic or haemorrhagic infarct, but she proceeded to receive thrombolysis in view of her symptoms. Her blood workup was normal. The next day, she developed increased weakness of her right arm and leg. A repeat CT scan was performed to rule out a post-lysis bleed, which was negative. An MRI was later performed, and no other abnormalities were detected. She exhibited a positive Hoover’s sign in the right leg and a diagnosis of functional neurological disorder (FND) was made. This condition can be characterised by a motor and sensory dysfunction, and loss of consciousness. Its presentation can be chronic or acute. Although the prevalence of FND is not entirely known, it is thought to be the second most common reason for neurology outpatient appointments after migraine and headache. It is rarely seen in children and tends to affect more women than men. This case highlights the importance of acknowledging functional neurological disorder as a differential diagnosis of unilateral weakness to avoid further unnecessary investigations or interventions. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S7